Использование низкотемпературной плазмы для получения зольных микросфер; Известия вузов. Физика; Т. 59, № 9, ч. 3 - Шеховцов В. В. Валентин Валерьевич; Власов В. А. Виктор Алексеевич; Волокитин Г. Г. Геннадий Георгиевич; Волокитин О. Г. Олег Геннадьевич (2016, 2016)
Заглавие с экрана